Study of Adsorption from Dilute Aqueous Solutions on to Activated Carbon. Part 2. Some Exotic Adsorption Isotherms - R. Mészáros; M. Nagy; G. Veress (Adsorption Science & Technology)
Adsorption isotherms for the adsorption of 1-propanol and 2-propanol from dilute aqueous solution on to two types of activated carbon were presented at fixed different initial concentrations. The confidence limits for the specific excess relative to these fixed initial concentrations were also given. The high precision calculation of these error terms was based on the model description of the equilibrium concentration versus sorbent concentration curves discussed previously. The Dubinin–Radushkevich representation of the adsorption data was presented and tested for the same adsorption data. It appears that in some cases the adsorbed amount as expressed by the specific excess depends not only on the equilibrium concentration of the supernatant solution but also on the initial concentration and sorbent concentration. The so-called characteristic isotherms were also calculated in order to compare the various adsorption systems.